Isolation and Identification of Biosurfactant Producing Bacteria from Slaughterhouse Wastewater - Kristina Sinaga; M. Hasbi; Eko Purwanto (Ilmu Perairan (Aquatic Science), 2021)
The slaughterhouse wastewater is rich of oil and fat and it may inhabit by biosurfactant producing bacteria. Isolation of the bacteria is needed in order to find out a biosurfactant producing bacteria that can be used to maintain the oil and fat polluted area through bioremediation process. To isolate and identify the biosurfactant-producing bacteria, a study has been conducted on July to September 2020. The samples were obtained from slaughterhouse wastewater at Cipta Karya street Pekanbaru, Riau Province and samplings were conducted three times. The isolation was conducted by TSB (Tryptic Soy Broth)  and incubated for 24 hours. Then the bacterial samples were planted by TSA (Tryptic Soy Agar)  and isolated for 24 hours. Then, it was identified using biochemical and morphological tests were carried out to find out the types of bacteria. The Emulsification Index was then calculated by using TSB (Tryptic Soy Broth) and kerosene. Results shown that the emulsification index were Flavobacterium 53%, Agrobacterium 53%, Serratia 60%, Salmonella 52. 5%, Salmonella 52.4%, Proteus 65.7%, Clostridium 62% and Aeromonas 59.5%. As Proteus is shown the highest Emulsification Index, it was check using a PCR (Polymerase Chain Reaction) and it is proved that the species is Proteus vulgaris